2022
DOI: 10.3390/ijms231810512
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Fitness Analysis through Interspecific Hybrid Progenies of Transgenic Brassica napus and B. rapa L. ssp.

Abstract: Interspecific hybridization between transgenic crops and their wild relatives is a major concern for transgene dispersal in the environment. Under controlled conditions, artificial hand pollination experiments were performed in order to assess the hybridization potential and the fitness of interspecific hybrids between Brassica rapa and genetically modified (GM) Brassica napus. Initially, six subspecies of B. rapa were hybridized with GM B. napus through hand pollination. In the resulting F1 hybrids, the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…A recent study showed that the F1 crop wild hybrid between oilseed rape and wild turnip can produce several viable and fertile generations being able to transfer the herbicide-resistant genes to their progenies. However, it was observed that the following generations decreased in tness compared with the F1 hybrid (Sohn et al 2022). Furthermore, other authors maintained that rst-generation hybrids have a reduced fertility, features that must be overcome in subsequent backcross generations for stable introgression to occur (Warwick et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A recent study showed that the F1 crop wild hybrid between oilseed rape and wild turnip can produce several viable and fertile generations being able to transfer the herbicide-resistant genes to their progenies. However, it was observed that the following generations decreased in tness compared with the F1 hybrid (Sohn et al 2022). Furthermore, other authors maintained that rst-generation hybrids have a reduced fertility, features that must be overcome in subsequent backcross generations for stable introgression to occur (Warwick et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Characterization of the tness cost in a feral population associated with the acquisition of herbicide-resistance genes provides an evolutionary framework needed to assess their impact on the environment and ecology (Sohn et al 2022). A recent study showed that the F1 crop wild hybrid between oilseed rape and wild turnip can produce several viable and fertile generations being able to transfer the herbicide-resistant genes to their progenies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…napus (AACC, 2n = 4x = 38) is one of the most important oilseed crops, which is widely cultivated in China. B. rapa (AA, 2n = 2x = 20) is frequently used as an important genetic resource for the genetic improvement of B. napus [32][33][34]. In this study, a synthetic hybrid (AAC, 3x = 29) was constructed by hybridization between B. napus (maternal parent) and B. rapa (parental parent).…”
Section: Introductionmentioning
confidence: 99%